PERAN GURU DALAM MENANGANI SISWA DISLEKSIA STUDI SDN KADUAGUNG - Erna Juherna; Alifah Nur habibah; Fajar Fajriyansyah; Fuji Rahmawati; Meilani Eka Saputri; Rahma Ayu Fauziyah; Riski Nur Ramdani; Siti Fatimah; Siti Hamidah Rohmah; Tri Maulani Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Dyslexia is a specific learning disability that makes it difficult for children to read, write, and spell, even though their brain capacity is otherwise normal. In elementary schools, the problem is often that teachers lack understanding and appropriate strategies for handling dyslexic students, so learning cannot truly meet their needs. This study will describe the role of teachers and the learning strategies used to address dyslexic students at Kaduagung Elementary School. We used a qualitative approach, focusing on teachers and fourth-grade students with dyslexia. Data collection was conducted through observation and interviews. Results showed that dyslexic students often have difficulty distinguishing similar letters and spelling words, and are easily distracted while learning. Causes can be genetic, low motivation to learn, or family environment. Teachers play a role through special mentoring, developing reading habits, using multisensory methods and audio-visual media, and providing extra time for learning. These strategies can help gradually improve students' literacy skills and self-confidence.